Supercharged diesel powertrain intake manifold analytical model - Faris, Waleed Fekry; Rakha, Hesham A.; Elmoselhy, Salah A.M. (Inderscience Enterprises Ltd., 2014)
Diesel powertrains are some of the most well-established yet promising technologies for their many advantageous features. Although vehicle analytical models accurately describe the physical phenomena associated with vehicle operation following from the principles of physics and with explainable mathematical trends, no analytical microscopic model has been developed as yet of diesel powertrains. The present research paper presents an analytical model of the intake manifold of a supercharged diesel powertrain, equipped with an electronic throttle control (ETC). The present study analytically modelled the intake manifold dynamic pressure, the mass flow rate of air entering the cylinders, the mass flow rate at the throat of the intake manifold, the intake manifold dynamic pressure under both transient choked and nonchoked conditions as well as under steady state condition, and the intake manifold gas speed dynamics. A case study has been conducted in order to experimentally validate the analytical model of the air acceleration in intake manifold with a deviation of 12.7%. The developed models serve to analyse the performance of the supercharged diesel intake manifold with respect to both the transient response and the steady state response. The present analytical models can help as well in developing and assessing diesel powertrain intake manifold technologies.